POTENTIAL OF PODCASTING TECHNOLOGY IN FORMATION OF FOREIGN LANGUAGE COMPETENCE OF FUTURE TRANSLATORS - Ковтун, Олена Віталіївна; Гармаш, Тетяна Андріївна; Хайдарі, Наталія Ігорівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
Shift of educational paradigm from traditional to student-centered, transition to new educational standards require that higher education institutions improve the quality of future specialists training, implement innovative learning technologies into the educational process, redouble attention to self-directed learning of students, introduce elements of distance learning. The purpose of the article is to find out the potential of podcasting technology in the formation of foreign language communicative competence of students-future translators. To achieve the purpose of the research the following theoretical and empirical methods were used: theoretical analysis, which allowed to clarify the essence of podcasting technology in the foreign language learning, its advantages and disadvantages; interviewing and observation over the educational process, which made it possible to determine the feasibility of podcasting technology in the educational process; pedagogical experiment thanks to which the hidden potential of innovative educational podcasting technology in the formation of foreign language communicative competence of students is revealed. The advantages (possibility to involve students into work with authentic materials, providing informal learning, formation of students ideas about the diversity of dialects and variants of a foreign language, efficiency of use) and disadvantages (lack of an automatized system for verifying the accuracy of responses and counting the number of attempts to perform tasks and reviewing the interview, report on nomenclature of mistakes, frequency of tasks’ accomplishment during a term) in the use of podcasting technology in organizing self-directed learning and distance learning of students were determined. The experience of using the German-language educational resource "The Easy German Podcast", English-language podcasts “Speakout” (Pearson) and news podcast "CNN 10" in the organization of self-directed learning of the disciplines "Practical course of a second foreign language and translation (German)" and "Practice of oral and written speech (English)" is revealed. The structure and components of the studied podcasts were highlighted, illustrative material in the form of printed examples-transcripts was offered, methodical recommendations for technology introduction into the educational process were given. The conducted experimental research proved that introduction of podcasting technology in the process of self-directed and distance learning of students majoring in 035 "Philology" has a positive effect on the formation of foreign language communicative competence of students, enriches their vocabulary, improves grammar skills, expands the range of linguistic and cultural knowledge, and promotes development of intercultural communication skills